Ipso-Bromination/iodination of arylboronic acids: Poly(4-vinylpyridine)-Br2/I2 complexes as safe and efficient reagents. Issue 38 (19th September 2019) - Fu, Fang; Gurung, Laxman; Czaun, Miklos; Mathew, Thomas; Prakash, G.K. Surya
Graphical abstract: Highlights: Stable poly(4-vinylpyridine)-Br2 /I2 complexes. Shelf stable electrophilic halogenating reagents. Facile ipso -bromination/iodination of aryl boronic acids. Mild reaction conditions tolerating various functional groups. Abstract: Poly(4-vinyl pyridine) supported bromine/iodine complexes were prepared and probed for ipso -bromination/iodination of arylboronic acids. These solid complexes with catalytic amount of additive are found to be safe and efficient reagent system for the ipso -bromination/iodination. The reaction occurs under mild conditions and tolerates various functional groups resulting in products with high selectivity and yields.